Identificación y elaboración de productos turísticos para el cantón Sigchos. - Pérez Hernández, Bryan Aron (2023)
The present investigation had as objective the elaboration of tourist products of the Sigchos canton, that is why an analysis of the territory is approached, that allow to determine the strengths and weaknesses of this canton, Sigchos has a considerable number of natural and cultural attractions having as main natural attraction the Quilotoa Lagoon, the tourism only focuses on this attraction thus overshadowing the majority of attractions that on the part of the tourists are not taken as destination since the only promotion and diffusion of this product only focuses on the attraction before mentioned. In order to generate tourism products that can be marketed in the place under study and be taken advantage of by national and foreign tourists who decide to visit this canton. Thus, in the first objective, the inventory of tourist attractions was validated through the exploratory and bibliographic method, using various techniques such as interviews with key people, tourism technicians of the GAD who confirmed the information collected in primary sources such as the PDOT and PDT of the Sigchos canton, On the other hand, in the second objective, the Methodology for the planning of tourism products of Peru was used, The design of the tourism product was carried out through the steps established by the manual, resulting in three tourism products called "Living Culture", "First what is ours" and "The treasure of the Hanging Garden of the Andes" for the canton. Finally, the third objective was carried out with the SWOT Matrix tools of the tourism products obtained, then MEFE and MEFI evaluation matrices were elaborated to obtain as a result promotion and dissemination strategies such as dissemination through the media, training and talks, strategic alliances with governmental and non-governmental authorities.